2020
DOI: 10.18502/acta.v58i3.3775
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Administration of Duloxetine on Postoperative Pain After Laparoscopic Myomectomy

Abstract: The purpose of this study was to evaluate the effect of preoperative administration of duloxetine on postoperative pain after laparoscopic myomectomy. In this double-blind clinical trial study, 57 patients aged 18-55 years with ASA I or II undergoing laparoscopic myomectomy involved. The case group received oral duloxetine 60 mg, and the control group received placebo 2 hours before the surgery. Pain scores, total analgesic consumption during 24 hours, recovery discharging time, nausea, vomiting, dizziness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 8 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…The trial demonstrated a significant reduction in pain over time. Although there is a paucity of data, the available evidence suggests that in similar populations post-laparoscopy, pain tends to increase in the first two hours following surgery, even with the use of opioid analgesia 24 27 . Furthermore, although non-significant, it is of interest that for the entire sample regardless of intervention group that pain scores increased during the washout period (10–20 min).…”
Section: Discussionmentioning
confidence: 99%
“…The trial demonstrated a significant reduction in pain over time. Although there is a paucity of data, the available evidence suggests that in similar populations post-laparoscopy, pain tends to increase in the first two hours following surgery, even with the use of opioid analgesia 24 27 . Furthermore, although non-significant, it is of interest that for the entire sample regardless of intervention group that pain scores increased during the washout period (10–20 min).…”
Section: Discussionmentioning
confidence: 99%
“…29,30,32e36,38,39,45,48 Most trials (17 of 24; 71%) used general anaesthesia, five (21%) used local or regional anaesthesia, and two studies (8%) allowed the use of either general or regional anaesthesia. 31,36 Background analgesia included acetaminophen alone, 33,40,49,51 or in combination with NSAIDs (celecoxib 36 or metamizole 52 ), opioids (codeine, 30,34 tramadol, 38,42,45,48 fentanyl, 48,50 or oxycodone 45 ), or both, 31,39 and NSAIDs 37,41,43,47 or opioids (morphine or pentazocine) 29 alone. Four trials 32,35,44,46 did not report baseline analgesia.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four trials 32,35,44,46 did not report baseline analgesia. Opioids (morphine, fentanyl, 41,45 tramadol, 46 and pethidine 43,51 ) were used as rescue analgesia in 15 trials 30,34,36e38,40,41,43e48,50,51 ; combination of acetaminophen and opioids was used in two trials 33,39 and diclofenac in one trial 42 ; six trials 29,31,32,35,49,52 did not report rescue analgesia.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In laparoscopic myomectomy, postoperative pain can be relieved without affecting hemodynamics, sedation, or other side effects in patients who received duloxetine before surgery. 15 However, it has not yet been studied in laparoscopic cholecystectomies. Therefore, this study was designed to evaluate the effect of oral administration of preoperative duloxetine on postoperative pain and total analgesic requirement in the postoperative period in patients undergoing laparoscopic cholecystectomy as the primary objective.…”
mentioning
confidence: 99%